Feasibility of High-Dose Dobutamine Stress SSFP Cine MRI at 3 Tesla with Patient Adaptive Local RF Shimming using Dual-Source RF Transmission: Initial Results - Strach, K.; Clauberg, R.; Müller, A.; Wonneberger, U.; Naehle, C. P.; Kouwenhoven, M.; Gieseke, J.; Schild, H. H.; Thomas, D. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To investigate the feasibility of high-dose dobutamine stress (HDDS) imaging using SSFP sequences at 3 T employing patient-adaptive local RF-shimming using a dual-source RF transmission system.Materials and Methods: 13 Patients underwent a HDDS protocol on a 3 T MRI scanner (Achieva 3.0T-TX, Philips Healthcare), equipped with a dual-source RF transmission system. SSFP cine sequences using patient-adaptive local RF-shimming (RF-S) were compared to cine images acquired without additional shimming. Image quality was evaluated on a 4-point grading scale and number of non-diagnostic segments assessed. Contrast (CN) between myocardium (SIM) and blood pool (SIB) was calculated [(SIB-SIM)/(SIB+SIM)].Results: Image quality both at rest and maximum stress was significantly improved with RF-S (ED:3.56 ± 0.5 vs. 3.23 ± 0.63; ES:3.4 ± 0.5 vs. 3.1 ± 0.7) compared to no RF-S (ED:2.9 ± 0.72 vs. 2.15 ± 0.78; ES:2.64 ± 0.74 vs. 1.95 ± 0.76; p < 0.01). The amount of non-diagnostic segments was significantly reduced when using RF-S at rest and stress (3 vs. 39; 19 vs. 78, p < 0.05). All HDDS studies were diagnostic if performed with RF-S (n = 13/13) in comparison to conventional shimming (n = 5/13). Image contrast was improved for SSFP sequences with RF-S (0.53 ± 0.08) compared to conventional images (0.46 ± 0.09, p = 0.06).Conclusion: Patient-adaptive local RF-shimming using a dual-source RF transmission system allows for reliable SSFP imaging in a clinical high-dose dobutamine stress protocol at 3 T. RF-S significantly improves image quality and reduces the number of non-diagnostic myocardial segments.
Keywords: patient-adaptive local RF-shimming; high-dose dobutamine stress testing; cardiac MRI; 3.0 Tesla; steady state free precession sequences; dual-source RF transmission